2012
DOI: 10.1007/s10661-012-2802-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality: a fusion of geochemical and geophysical information via Bayesian neural networks

Abstract: Deplorable quality of groundwater arising from saltwater intrusion, natural leaching and anthropogenic activities is one of the major concerns for the society. Assessment of groundwater quality is, therefore, a primary objective of scientific research. Here, we propose an artificial neural network-based method set in a Bayesian neural network (BNN) framework and employ it to assess groundwater quality. The approach is based on analyzing 36 water samples and inverting up to 85 Schlumberger vertical electrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Other studies have reported similar results describing water quality indices developed based on ANNs and ANFIS [2,30,31]. The ability of the ANN and ANFIS models to simulate the concentration values of EC and TDS at the Langat Basin were excellent ( Table 3 and Figs.…”
Section: Resultssupporting
confidence: 65%
“…Other studies have reported similar results describing water quality indices developed based on ANNs and ANFIS [2,30,31]. The ability of the ANN and ANFIS models to simulate the concentration values of EC and TDS at the Langat Basin were excellent ( Table 3 and Figs.…”
Section: Resultssupporting
confidence: 65%
“…The pH value in the study area ranges from 5.81 to 6.98. The pH concentration indicates that the groundwater is relatively acidic in Kondura (pH value 5.81), Mochemar (pH value 5.92), Kelus (pH value 5.98), Humarmala (pH value 6.34) and Nerur (pH value 6.36) than the rest of the places (Maiti et al, 2012). The geochemical analysis of groundwater samples further corroborates with the findings of resistivity studies and emphasizes the extent of saline water intrusion into the mainland.…”
Section: Profile Esupporting
confidence: 74%
“…The western part (VES stations 1 and 29) is encroached by saline water presumably due to the vicinity of Arabian Sea. Geochemical analysis of groundwater in the study area (Maiti et al, 2012) reported that the electrical conductivity (EC) ranged between 70 and 4,450 µS/cm (mean =421.47 ìS/cm). The EC values recorded at VES points 2, 5, 26 and 29 falls beyond the acceptable level for drinking prescribed by World Health Organization (WHO, 1984), and were attributed due to the intrusion of saline water from Arabian Sea.…”
Section: Longitudinal Unit Conductance Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Langenegger (1990) classification, the majority of the samples fall under saline category (1500-10,000 μS/cm). TDS is regarded as one of the key factors which decide the use of groundwater for any purpose (Maiti et al, 2013). The TDS value of surface water (November 2011) and groundwater found during November 2012 and 2013 exceeds the acceptable limit of 500 mg/L.…”
Section: Groundwater Chemistrymentioning
confidence: 99%